Conceptual Framework: Measuring Police Performance and Efficiency. The Types of “Quality” Indicators in Foreign Researches - Vári, Vince (Magyar Rendészet, 2018)
The “orthodoxy” of efficiency is essentially nothing else than the practical and rational usage of resources and expences/costs in order to produce the desired product or service. Its axiom is that all production branches, processes and services need to be rationalized, for which inputs/expenditures can be minimalized and profits can be maximalized. Whether the police, as a safety supplier, in their own social context/environment (in case of service users) and in order to increase satisfaction and trust (I mean profit), exploit all the opportunities (i.e. make optimal use of the conditions, that is rationalize) that socially and politically determine their organizational structure and operation. In order to interpret the frames of an efficient police, it is important to identify the targets of law enforcing, because efficiency can only be evaluated in the dimension of achieving those targets. It cannot be anything else than complying with the law, ensuring the rule of law and the protection of human rights as constitutionally identified targets. Therefore, traditional market instruments are not suitable for measuring the quality and efficiency of the police. In order to talk about efficiency measurement, it is necessary to develop the indicators that, in line with the social aims of the police, are suitable to show the defence capabilities of law enforcement. Therefore, at the forefront of our research the social purposes are significant, not the organizational ones. Organizational purposes can be considered as the indicators of inner effectiveness, as a quality index. Producing performance values specified by the organization itself within the burocratic framework, however, may easily conflict with the effectiveness interpretations of other fields of justice, but mainly those expressed by the society. Therefore, developing the indicators that indicate the quality of its social functioning and effects is crucial, not its organizational one. “Until the police measure their own performance by their own standards, they will not be able to get an objective picture about the fulfillment of their own social role.” In that regard, by qualitative indicators we mean the results and effectiveness of the fulfillment of social purposes.